THEORETICAL APPROACH TO PHRASEOLOGICAL UNITS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article is dedicated to phraseology section of linguistics, which examines the theoretical views of different periods of world linguists on the term and their enrichment over the years.